The Impact of Fatherless On Authentic Happiness in Female Students At State Vocational School 1 Binjai - Muhammad Ridwan; Nurul Hasanah; Lendra Faqrurrowzi (Universitas Negeri Medan, 2025)
This study aims to determine the impact of Fatherless on Authentic Happiness in female students at SMK Negeri 1 Binjai and uses a quantitative method with a purposive sampling technique. The data collection technique uses a questionnaire distribution using Google Form. The sample of this study amounted to 47 female students of class XII SMK Negeri 1 Binjai. To test the hypothesis proposed in this study, the study used the help of the SPSS Statistic 23 software application for Windows 8. The findings of this study are: (1) The significance value obtained by the variable is smaller than the reference value, namely 0.000 <0.05 so it can be concluded that there is an Impact of Fatherless on Authentic Happiness in female students at SMK Negeri 1 Binjai. (2) The results of the R Square test are 9% of the Fatherless variable influencing Authentic Happiness in female students, the rest is influenced by other variables not examined in this study. (3) Anova table obtained a significance value = 0.031 while the H_o criteria are rejected if p < 0.031. So, the results of this simple regression test can be interpreted that H_a which states that the Impact of Fatherless influences Authentic Happiness in female students is accepted, and the consequence of H_o is rejected. So it can be said that the proposed hypothesis is that there is an Impact of Fatherless on Authentic Happiness in female students at SMK Negeri 1 Binjai.